When vegetarians eat meat: Why vegetarians violate their diets and how they feel about doing so. (1st December 2019) - Rosenfeld, Daniel L.; Tomiyama, A. Janet
Abstract: Many people who self-identify as vegetarian actually eat meat on occasion. Surveys documenting this phenomenon have become abundant over the past two decades, and recent studies have begun to explain why some vegetarians are more likely to violate their diets than others are. However, qualitative research detailing the experiences of vegetarians eating meat is sparse. In the current study, we surveyed 243 vegetarians, 124 (51%) of whom indicated that they have eaten meat since going vegetarian. Of these 124 participants, 108 provided written narratives about their experiences eating meat, which we analyzed. Participants were most likely to eat meat at family gatherings and on special occasions; to eat meat in order to make a social situation flow more smoothly; and to react negatively to having eaten meat. Participants' narratives suggest that vegetarianism may be best conceived as a social identity, beyond just a diet. Some vegetarians reported that they view their diets as flexible guidelines, rather than rigid rules they ought to follow without exception. This study is the first, to our knowledge, to document in detail how vegetarians reflect on their experiences eating meat.